Evaluation Of Islamic Religious Education Materials In Higher Education: An Overview Of State Universities In North Sumatra - Budianti, Yusnaili; Mahmud, Salami; Rois, Nur; Jali, Jafalizan Md (STKIP Singkawang, 2024)
Islamic religious education (PAI) is very important for students and lecturers because it can form people who are devout and obedient to Allah Subhanahu Wa Ta’ala, in carrying out their worship by emphasizing the development of the Muslim personality, namely the development of akhlaqul karimah. This research was conducted with the aim of evaluating the content of Islamic religious education (PAI) material at state universities in North Sumatra. The research method used is a descriptive qualitative method, with data collection techniques involving observation, Focus Group Discussion (FGD), interviews and questionnaires. Data analysis was carried out through reduction stages, data presentation and drawing conclusions. The research results show several main findings: First, validity analysis shows that PAI material at state universities in North Sumatra can be considered good for PAI learning. Second, from the practicality analysis based on student responses, it was found that PAI material had a good level of practicality. Overall, this research highlights the potential to improve the quality of PAI learning materials at state universities in North Sumatra. Recommendations for improvement include updating the curriculum, adjusting the amount of material, and increasing the attractiveness and relevance of the material to students' daily lives.